Efficient separation of benzene and cyclohexane by liquid liquid extraction using emerging solvents and their binary mixtures / Muhammad Zulhaziman Mat Salleh - Muhammad Zulhaziman , Mat Salleh (2019)
The separation of benzene and cyclohexane is difficult to perform via conventional distillation because of their close boiling points. The use of conventional technology in industry suffers from several disadvantages such as process complexity, high capital and operating costs, and high energy consumption. Ionic liquids (ILs) and deep eutectic solvents (DESs) are two types of emerging solvents being widely studied in many applications. In this study, 40 DESs and more than 200 ILs were separately screened using COSMO-RS program for the separation of benzene and cyclohexane by liquid–liquid extraction process. The screening was evaluated based on the comparison of selectivity, capacity, and performance index; all derived from the activity coefficient at infinite dilution. The actual performance of the top-screened solvents, i.e. 5 DESs and 4 ILs was validated via experimental liquid–liquid extraction process at 25 oC and under 1 atm. The selected DESs in this study, namely tetrabutylammonium bromide:sulfolane, TBABr:Sulf (1:7); tetrabutylammonium bromide:triethylene glycol, TBABr:TEG (1:4); methyltriphenylphosphonium bromide:triethylene glycol, MTPPBr:TEG (1:4); methyltriphenylphosphonium bromide:1,2-propanediol, MTPPBr:PD (1:4); and choline chloride:triethylene glycol ChCl:TEG (1:4), were proved to be feasible extracting solvents. Despite the small benzene distribution ratio, an effective extraction using TBABr:Sulf (1:7) was still achievable through a multistage process, where 97% of benzene were extracted after nine extraction stages. In addition, TBABr:Sulf (1:7) can be easily recovered and regenerated back into the next extraction cycle. After four cycles, the recycled DES was as effective as the fresh one; the extracted benzene was constantly higher than 98 %. The analysis of extraction mechanism proved that the TBABr:Sulf (1:7) conserves its structure in the presence of benzene, thus prevents the solubilisation of sulfolane in the raffinate phase. In the study of extraction using IL, four ILs, namely 1-ethyl-3-methylimidazolium acetate, C2mimAc; 1-ethyl-3-methylimidazolium dicyanamide, C2mimN(CN)2; 1-ethyl-3-methylimidazolium thiocyanate, C2mimSCN; and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, C2mimTf2N, were selected based on the COSMO-RS preliminary screening. The new ternary LLE data for each IL was measured experimentally and correlated successfully with the NRTL model, where the root mean square deviation (RMSD) between experimental and calculated solubilities was less than 1%. On top of being commercially available at relatively low prices, the selected ILs showed effective extraction of benzene. The comparison of these ILs with other solvents in the literature proved their relative superiority with respect to extraction efficiency. Finally, mixtures of binary solvent were developed under the same condition by utilizing the high individual value of selectivity or distribution ratio of the single IL. Six new pseudo-ternary LLE data involving binary mixtures of [IL–organic solvent] or [IL–IL] were generated. Ethylene glycol was discovered as a good diluting agent with C2mimTf2N, indicating a potential cost saving. At the optimized mixing fraction, the mixture of [C2mimTf2N + C2mimSCN] produced the highest extraction performance, giving benzene distribution ratio of 0.96 and selectivity of 20.7. The mixing of different solvents has been proved to be a newly efficient and versatile method to further enhance the extraction performance.